2010
DOI: 10.1002/jcc.21516
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on the mechanism and kinetics of Cl reaction with C2H5I

Abstract: The dual-level direct kinetics method has been used to investigate the multichannel reactions of C(2)H(5)I + Cl. Three hydrogen abstraction channels and one displacement process are found for the title reaction. The calculation indicates that the hydrogen abstraction from -CH(2)- group is the dominant reaction channel, and the displacement process may be negligible because of the high barrier. The rate constants for individual reaction channels are calculated by the improved canonical variational transition-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The atmospheric lifetime of CH 3 CH 2 I (at 298 K) initiated by ⋅Cl was evaluated to be 206.68 day ([⋅Cl]=1.0×10 4 molecule cm −3 ) [39] according to the rate constant (5.60×10 −12 cm 3 molecule −1 s −1 ) obtained by Jia et al. [40] . This shows that ⋅OH is more favorable than ⋅Cl in the degradation of CH 3 CH 2 I. Bai et al [20] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric lifetime of CH 3 CH 2 I (at 298 K) initiated by ⋅Cl was evaluated to be 206.68 day ([⋅Cl]=1.0×10 4 molecule cm −3 ) [39] according to the rate constant (5.60×10 −12 cm 3 molecule −1 s −1 ) obtained by Jia et al. [40] . This shows that ⋅OH is more favorable than ⋅Cl in the degradation of CH 3 CH 2 I. Bai et al [20] .…”
Section: Resultsmentioning
confidence: 99%
“…The atmospheric lifetime of CH 3 CH 2 I (at 298 K) initiated by * Cl was evaluated to be 206.68 day ([ * Cl] = 1.0 × 10 4 molecule cm À 3 ) [39] according to the rate constant (5.60 × 10 À 12 cm 3 molecule À 1 s À 1 ) obtained by Jia et al. [40] This shows that * OH is more favorable than * Cl in the degradation of CH 3 CH 2 I. Bai et al [20] have evaluated the NO [41][42][43][44] Comparing the atmospheric lifetimes of CH 3 I and CH 3 CH 2 I initiated by * OH or NO 3 * radicals, it can be found that the introduction of À CH 3 can significantly shorten the atmospheric residence time of iodoalkanes and accelerate the formation of reactive iodine-containing radicals, promoting the iodine cycling process in the atmospheric environment.…”
Section: Atmospheric Lifetimementioning
confidence: 99%
“…High concentrations of Cl atoms can be found in marine environments and urban areas with high levels of chloride‐containing aerosol 11. 12, 26 The reactions of FESs with Cl and OH radicals are important to evaluate the atmospheric lifetime of the FESs. CF 3 COOCH 2 CH 3 , CF 2 HCOOCH 3 , and CF 3 COOCH 3 are the typical FESs; thus, we take attention to the three FESs reactions with chlorine atoms and hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%